Bifunctional Amine‐Squaramides: Powerful Hydrogen‐Bonding Organocatalysts for Asymmetric Domino/Cascade Reactions. Issue 2 (15th January 2015) - Chauhan, Pankaj; Mahajan, Suruchi; Kaya, Uğur; Hack, Daniel; Enders, Dieter
Abstract: Organocatalytic domino/cascade reactions provide a convenient method for the construction of complex molecular structures bearing multiple stereocenters in a highly stereoselective fashion. Among various organocatalysts, bifunctional squaramides have emerged as powerful hydrogen‐bonding catalysts for promoting a wide array of useful asymmetric organocascade sequences. Higher activity and ease of preparation make these catalysts excellent alternatives for thiourea‐based organocatalysts. This review highlights the advances in the rapidly growing field of amine‐squaramide‐catalyzed domino/cascade reactions and their mode of action. Abstract :